2017
DOI: 10.3390/ma10060610
|View full text |Cite
|
Sign up to set email alerts
|

The Preparation of Porous Sol-Gel Silica with Metal Organic Framework MIL-101(Cr) by Microwave-Assisted Hydrothermal Method for Adsorption Chillers

Abstract: Metal organic framework (MOF) of MIL-101(Cr)-Silica (SiO2) composites with highly mesoporous and uniform dispersions were synthesized by a microwave-assisted hydrothermal method followed by the sol-gel technique. Water vapor adsorption experiments were conducted on the MIL-101(Cr)-SiO2 composites for industrial adsorption chiller applications. The effects of MIL-101(Cr)-SiO2 mixing ratios (ranging from 0% to 52%), the surface area and amount of Lewis and Brønsted sites were comprehensively determined through w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 53 publications
2
4
0
Order By: Relevance
“…A peak at 1681.7 cm -1 is assigned to the carboxyl group C=O in the organic linker. These are all consistent with previous results which confirms that MIL-101(Fe) was successfully synthesized [8,14].…”
Section: Resultssupporting
confidence: 93%
“…A peak at 1681.7 cm -1 is assigned to the carboxyl group C=O in the organic linker. These are all consistent with previous results which confirms that MIL-101(Fe) was successfully synthesized [8,14].…”
Section: Resultssupporting
confidence: 93%
“…3f. 54,79 The green solids isolated from reaction mixtures containing 1.25% TEAOH solutions were also characterised through Field Emission Scanning Electron Microscopy (FESEM) (Fig. 4) and Transmission Electron Microscopy (TEM) (Fig.…”
Section: Scalable and Less Toxic Mil-101(cr) Synthesismentioning
confidence: 99%
“…Silica can be used to enhance the water stability of MOFs, and their composites can be used to adsorb water or other moist gases. Using a microwave-assisted sol-gel process, Uma et al fabricated an MIL-101(Cr)-SiO 2 composite with uniform mesopores; they found that the material has high adsorption efficiency to water vapor, and the water stability of the composite is significantly enhanced by the addition of silica [68]. Mazaj et al first prepared amino-functionalized MOFs by modifying FDU-12 with aminopropyltriethoxysilane; then, the MOFs were immersed into a Cu 2+ solution to obtain an HKUST-1@NH 2 -FDU-12 composite material with copper ions as ligands (Figure 8) [112].…”
Section: Application Of Mof/silica Compositementioning
confidence: 99%